Agronomic evaluation of mustard planter for enhancing production efficiency of Indian mustard (Brassica juncea) - JAT, R S; SINGH, DHIRAJ; JAT, M L; SINGH, V V; SINGH, H V; SHARMA, PANKAJ; RAI, P K (The Indian Journal of Agricultural Sciences, 2021)
Indian mustard [Brassica juncea (L.) Czern & Coss.] is traditionally sown either by broadcasting or with ordinary wheat seed drill having drawbacks of high seed rate, seed breakage, less seed germination, uneven and dense plant population resulting into low seed yield. A Mustard Planter was developed and evaluated at research station as well as farmers’ field against wheat seed drill (farmer’s practice) during 2016-18 to vanquish the pre-taxed constraints in Indian mustard. Results showed significant improvement in branches per plant, girth of basal node, leaf area index (LAI), relative water content (RWC), seed yield, harvest index, test weight and accrued higher benefit margin in the station trials. Farmer’s field trials also recorded optimum plant population, higher plant height, branches per plant and stem girth. Mustard Planter sown crop recorded more seed yield (+9-22%), harvest index (+11.7%), Test weight (+13.6%), net return (+13.3-30.6%) and B/C ratio (+16%) in the station as well as farmer’s field trials. The fields sown with Mustard Planter also conserved soil moisture (>100%) over wheat seed drill in 0-60 cm soil depth during the crop mid-season. The results endorsed that the Mustard Planter is an efficient seeding machine for sowing of rapeseed-mustard in the rainfed situation and may be recommended for its wider adaptability in the region for the benefit of the farmers.